Integrated stratigraphy of St. Thomas Section (Malta): new preliminary data on potentially section for the Burdigalian GSSP - BALDASSINI, NICCOLO'; FORESI, LUCA MARIA; MAZZEI, ROBERTO; SALVATORINI, GIANFRANCO; VERDUCCI, MARINA; Caricchi C.; Da Prato S.; Di Stefano A.; Ferraro L.; Lirer F.; Sagnotti L. (University of Edinburgh, 2012)
The GSSP of the Burdigalian stage has still not been ratified and has been temporarily placed in correspondence of the First Occurrence (FO) of the calcareous nannofossil species Helicosphaera ampliaperta at 20.43 Ma by Lourens et al. (2004). Here we present the preliminary integrated bio-magnetostratigraphic results obtained from the study of the early Miocene St. Thomas section, outcropping on the southern coast of Malta Island (central Mediterranean basin). In this area, the section represents the whole Middle Globigerina Limestone member (the intermediate member of the Globigerina Limestone formation, Chattian – Langhian in age), from the basal phosphate rich bed (the QCB of Rose et al., 1992) up to the highly eroded surface (the TMGLOg of Gruszczynsky et al., 2008). The succession, ~90m thick, is composed of alternating marls and calcareous marls and 744 samples were collected by a hand-core driller system, with a stratigraphic spacing of ~10 cm. Micropalaeontological assemblages are rich and often well-preserved and suitable for a quantitative analysis; furthermore, magnetostratigraphical analyses were also carried out and produced reliable results. These analysis allowed us to attribute the St. Thomas deposits to the MMi2 planctonic foraminiferal Zone of Iaccarino et al. (2007) and to the calcareous nannofossil MNN2a Zone (upper part) – MNN4a Zone (lowermost part) interval of Fornaciari and Rio (1996). In terms of magnetostratigraphy, it extends from the Magnetochron C6n to the Magnetochron C5Dn. The well exposed outcrops, the lithological cyclicity, the rich and well preserved calcareous plankton assemblages and the reliable magnetostratigraphic data make this section potentially suitable for high-resolution stratigraphic, cyclostratigraphic and astrochronologic studies.